Autotrophic cultivation of Spirulina platensis for CO 2 fixation and phycocyanin production - Zeng, X.; Danquah, Michael; Zhang, S.; Zhang, X.; Wu, M.; Chen, X.; Ng, I.; Jing, K.; Lu, Y. (Elsevier BV, 2012)
Microalgae biotechnology provides a new industrial paradigm that simultaneously yields various vital products and captures CO 2 in a single process. Development of optimal strategies to harness microalgal resources is critical to full-scale production and application of microalgae-derived products. This work parametrically investigated the autotrophic cultivation of Spirulina platensis for enhanced simultaneous CO 2 fixation and phycocyanin production using conical flasks and newly designed photobioreactors. In the absence of culture aeration in the conical flasks, a maximum biomass concentration of 3.20g/L was achieved under alkaline conditions with initial pH of ~9. In the presence of culture aeration, a maximum biomass concentration of 5.96g/L was obtained under intermittent CO 2 supply at 20mM/(L2d) (that is 20mM/L every other day). Continuous sparging of 0.1L/min compressed air in combination with 20mM/(Ld) intermittent CO 2 supply into a customarily designed photobioreactor resulted in biomass and crude phycocyanin concentrations of 5.92g/L and 1.06g/L respectively. Further photobioreaction optimization resulted in biomass and phycocyanin concentrations of 7.27g/L and 1.22g/L respectively using 20mM/Ld CO 2 intermittent aeration supplemented with continuously supplied compressed air under specific flow conditions. The highest volumetric titre of phycocyanin obtained in this work is amongst the highest reported in literature. These results indicate that high biomass, phycocyanin concentration and CO 2 fixation rate could be obtained with minimal extra effort simply by optimizing bioprocess conditions. The growth results of S. platensis cultivation fitted well to the logistic rate equation. © 2011 Elsevier B.V.